T‐lymphocyte and glycemic status after vitamin D treatment in type 1 diabetes: A randomized controlled trial with sequential crossover. Issue 3 (6th December 2016) - Bogdanou, D.; Penna‐Martinez, M.; Filmann, N.; Chung, T.L.; Moran‐Auth, Y.; Wehrle, J.; Cappel, C.; Huenecke, S.; Herrmann, E.; Koehl, U.; Badenhoop, K.
Abstract: Background: Type 1 diabetes mellitus (T1D) is mediated by autoaggressive T effector cells with an underlying regulatory T‐cell (Treg) defect. Vitamin D deficiency is highly prevalent in T1D, which can aggravate immune dysfunction. High‐dose vitamin D treatment may enhance Tregs and improve metabolism in T1D patients. Methods: In a randomized double‐blind placebo‐controlled trial with crossover design, patients received either for 3 months cholecalciferol 4000 IU/d followed by 3 months placebo or the sequential alternative. Thirty‐nine T1D patients (19 women and 20 men) completed the trial. Results: Primary outcome was a change of Tregs, secondary HbA1C, and insulin demand. Effects were evaluated based on intra‐individual changes between treatment and placebo periods for outcome measures. Exploratory analyses included vitamin D system variant genotyping and C‐peptide measurements. Median 25(OH)D3 increased to 38.8 ng/ml with males showing a significantly stronger increase (p = .003). T‐lymphocyte profiles did not change significantly (p > 2); however, the intra‐individual change of Tregs between males and females was different with a significantly stronger increase in men (p = .017), as well as between genotypes of the vitamin D receptor (Apa, Taq, and Bsm: genotypes aa, TT, and bb; p = .004–0.015). Insulin demands declined significantly (p = .003–.039) and HbA1C improved (p < .001). Random C‐peptide levels were low but rising (median, 0.125 ng/ml; range, 0.02–0.3) in 6 patients. No toxicity was observed. Conclusion: A daily vitamin D dose of 4000 IU for 3 months was well tolerated and enhanced Tregs in males. Glucometabolic control improved in all. Subsequent larger trials need to address ß‐cell function and genotyping for individualized vitamin D doses.